A book of luminous things an international anthology of poetry - Milosz, Czeslaw (Orlando, Florida Harcourt Brace & Company, 1998)
For A Book of Luminous Things Nobel laureate poet Czeslaw Milosz has selected 300 of the world's greatest poems written throughout the ages, poems memorable for how they render the realities of the world palpable and immediate. They are organized under eleven headings - including "Epiphany," "Nature," "The Secret of a Thing," "Travel," "Places," and "The Moment." In addition to his introduction, Milosz contributes brief, penetrating commentary on each poet. Among the poets included are Elizabeth Bishop, William Blake, Joseph Brodsky, Constantinos Cavafy, Emily Dickinson, Robert Frost, Allen Ginsberg, Linda Gregg, Seamus Heaney, Zbigniew Herbert, Jane Hirshfield, Robinson Jeffers, D. H. Lawrence, Denise Levertov, Philip Levine, Li Po, Antonio Machado, Thomas Merton, W. S. Merwin, Sharon Olds, Mary Oliver, Po Chu-I, Rainer Maria Rilke, Theodore Roethke, Charles Simic, Gary Snyder, Wallace Stevens, May Swenson, Anna Swir, Wislawa Szymborska, Tu Fu, Wang Wei, Walt Whitman, and William Carlos Williams.
Epiphany. Maximus / D.H. Lawrence -- Kikaku -- Issa -- Music of spheres / Jean Follain -- In the middle of the road / Carlos Drummond de Andrade -- Nature. The author of American Ornithology sketches a bird, now extinct [and] Loons mating / David Wagoner -- A taxidermist / Jean Follain -- Irises / Li-Young Lee -- Like they say / Robert Creeley -- Moths / Adam Zagajewski -- The kingfisher / Mary Oliver -- In praise of self-deprecation [and] Four in the morning / Wislawa Szymborska -- Moss-gathering / Theodore Roethke -- Living / Denise Levertov -- Waxwings / Robert Francis -- A sleepless night / Philip Levine -- Late Spring / Robert Hass -- Orchards in July / Zbigniew Machej -- Dusk in winter / W.S. Merwin -- Butterfly / D.H. Lawrence -- Dragonfly / Gary Snyder -- Carnations / Theodore Roethke -- Carmel Point / Robinson Jeffers -- Daybreak / Galway Kinnell -- Mystic / D.H. Lawrence -- Honey / Robert Morgan -- Destruction / Joanne Kyger -- Wild geese / Mary Oliver -- Seen from above / Wislawa Szymborska -- A story / Jane Hirshfield -- Face the animal / Jean Follain -- Flight / Jorge Guillén -- A narrow fellow in the grass / Emily Dickinson -- The most of it / Robert Frost -- The sea and the man / Anna Swir -- The secret of a thing. I am the poet / Walt Whitman -- From "Milton" / William Blake -- The runner [and] A farm picture / Walt Whitman -- On a painting by Wang the clerk of Yen Ling / Su Tung P'o -- Bellrope / Robert Morgan -- The lightning; The sun; [and] The lute / Judah Al-Harizi -- Boats in fog [and] Evening ebb / Robinson Jeffers -- The image / Robert Hass -- Cobalt / Rolf Jacobsen -- Study of two pears / Wallace Stevens -- The red wheelbarrow / William Carlos Williams -- View with a grain of sand / Wislawa Szymborska -- The frog / Francis Ponge -- Facing Bonnard / Aleksander Wat -- Magnificent peak / Muso Soseki -- Witness / Denise Levertov -- Travel. Images / Valery Larbaud -- Aleutian Islands; Fish Cove; Harvest; South; [and] Frisco-City / Blaise Cendrars -- Ancient air / Li Po -- Coming at night to a fisherman's hut / Chang Chi -- Starting early [and] A dream of mountaineering / Po Chü-I -- Ancient air / Li Po -- Song of marching with the army [and] Watching the hunt / Wang Wei -- Recalling the past at T'ung Pass / Chang Yang-hao -- Express train / Rolf Jacobsen -- Rainbow at night / Antonio Machado -- Vacation / William Stafford -- The train stops at Healy Fork / John Haines -- Seen fleetingly, from a train / Bronislaw Maj -- A journey / Edward Field -- Along the Grand Canal / Ch'in Kuan -- Morning, sailing in Xinyang / Wang Wei -- On the mountain / John Haines -- We started home, my son and I / Jaan Kaplinski -- Places. The south / Wang Chien -- Travelling northward / Tu Fu -- After collecting the autumn taxes [and] Rain / Po Chü-I -- Another Spring / Tu Fu -- Exile in Japan / Su Man Shu -- In the Lake District [and] Odysseus to Telemachus / Joseph Brodsky -- After midnight / Louis Simpson -- A strange new cottage in Berkeley / Allen Ginsberg -- Prayer for my son / James Applewhite -- Madly singing in the mountains / Po Chü-I -- Brazil, January 1, 1502 / Elizabeth Bishop -- The catacombs in San Callisto / Rolf Jacobsen -- Greece / Gunnar Ekëlof -- Syros / Tomas Tranströmer -- Night music / Linda Gregg -- Auto mirror / Adam Zagajewski -- The plain / Sandor Weores -- Outskirts / Tomas Tranströmer -- To a French Structuralist / David Kirby -- Summer night / Antonio Machado -- A white turtle under a waterfall / Wang Wei -- Fisherman / Ou Yang Hsiu -- Old fisherman / Liu Tsung-Yüan -- Magnolia basin / Wang Wei -- The moment. Cavalry crossing a ford / Walt Whitman -- The mason / Aloysius Bertrand -- Signature of all things [and] The heart of Herakles / Kenneth Rexroth -- Sunset; Winter dawn; South wind; [and] Clear after rain / Tu Fu -- Late October camping in the Sawtooths / Gary Snyder -- Dusk in my backyard / Keith Wilson -- Late lights in Minnesota / Ted Kooser -- Tracks / Tomas Tranströmer -- Rubber / Rolf Jacobsen -- Zen of housework / Al Zolynas -- An August afternoon / Bronislaw Maj -- The window / Raymond Carver -- Buying; Black meat; [and] School and nature / Jean Follain -- A dark thing inside the day / Linda Gregg -- From "Songs of a wanderer" / Aleksander Wat -- The bridge / Oscar V. de L. Milosz -- My wife and children / Jaan Kaplinski -- By the bivouac's fitful flame / Walt Whitman -- Woman at lit window / Eamon Grennan -- Empire of dreams / Charles Simic -- Sleeping on horseback / Po Chü-I -- Of rain and air / Wayne Dodd -- Rain / Sandor Weores -- People among people. Song about Xi Shi [and] Dancing woman, cockfighter husband, and the impoverished sage / Wang Wei -- To Pi Ssu Yao / Tu Fu -- A dream at night / Mei Yao Ch'en -- From "Clearances," in memoriam M.K.H. (1911-1984) / Seamus Heaney -- Supplication / Constantine Cavafy -- From "I sing the body electric"; As toilsome I wander'd Virginia's woods; A sight in camp in the daybreak gray and dim; [and] Dirge for two veterans / Walt Whitman -- Proletarian portrait [and] To a poor old woman / William Carlos Williams -- The new wife / Wang Chien -- Love in the classroom / Al Zolynas -- Going blind / Rainer Maria Rilke -- Toast [and] Bladder song / Leonard Nathan -- Utterance / W.S. Merwin -- Notice / Steve Kowit -- The same inside / Anna Swir -- The card-players / Philip Larkin -- From "The sleepers" / Walt Whitman -- I wash the shirt / Anna Swir -- I go back to May 1937 / Sharon Olds -- A voice / Tadeusz Rozewicz -- An elegy for Ernest Hemingway / Thomas Merton -- A noiseless patient spider / Walt Whitman -- Woman's skin. In the morning / Steve Kowit -- Morning / Chu Shu Chen -- Cosmetics do no good / Steve Kowit -- Hopelessness / Li Ch'ing-chao -- The greatest love [and] She does not remember / Anna Swir -- Adult / Linda Gregg -- Thank you, my fate [and] The second madrigal / Anna Swir -- When he pressed his lips / Steve Kowit -- A mirror / Jean Follain -- Getting up in winter / Emperor Ch'ien-wen of Liang -- What chord did she pluck / Steve Kowit -- A woman meets an old lover / Denise Levertov -- Question / May Swenson -- Cremation / Robinson Jeffers -- A sketch for a modern love poem / Tadeusz Rozewicz -- I talk to my body; Troubles with the soul at morning calisthenics; [and] I starve my belly for a sublime purpose -- Situations. Dejeuner sur l'herbe / Tu Fu -- And with March a decade in Bolinas / Joanne Kyger -- A joke / Aleksander Wat -- The philosophers: Lao-tzu; Golden bells; [and] After getting drunk, becoming sober in the night / Po Chü-I -- Of his life / Wayne Dodd -- Wine / Raymond Carver -- Depiction of childhood / Franz Wright -- Teaching the ape to write / James Tate -- In praise of my sister / Wislawa Szymborska -- The sudden appearance of a monster at a window / Lawrence Raab -- Coming home late at night [and] Snow storm -- A leaf / Bronislaw Maj -- Poetry reading / Anna Swir -- Nonattachment. The cobweb / Raymond Carver -- Eye mask / Denise Levertov -- Climbing the Ling-Ying Terrace and looking north / Po Chü-I -- Magic Words / Eskimo (anonymous) -- From "The Torah of the void" / Nachman of Bratzlav -- Little by little, wean yourself / Jelaluddin Rumi -- For the anniversary of my death / W.S. Merwin -- Invocation of the Creator / Yoruba tribe -- Man is born in tao [and] The need to win / Chuang Tzu -- Out beyond ideas / Jelaluddin Rumi -- The birds have vanished / Li Po -- Contraband / Denise Levertov -- A ringing bell / Ch'ang Yu -- Lazy about writing poems; A farewell; [and] Drifting on the lake / Wang Wei -- Visitors / Tu Fu -- Lodging with the old man of the stream / Po Chü-I -- A ballad of going down to the store / Miron Bialoszewski -- Old man at leisure / Muso Soseki -- From "The city of the moon" [and] A long lifetime / Kenneth Rexroth -- The day we die / Southern Bushmen -- A prayer that will be answered / Anna Kamieńska -- History. Foundations / Leopold Staff -- I'm afraid of fire / Anna Swir -- From Persian parables / Aleksander Wat -- Above us / Julia Hartwig -- Perhaps... / Shu Ting -- I can't help you / Ryszard Krynicki -- Elegy of Fortinbras / Zbigniew Herbert -- The Armenian language is the home of the Armenian / Moushegh Ishkhan -- Ordinance on arrival / Naomi Lazard -- Waiting for the barbarians / Constantine Cavafy.
"A Harvest book."
Includes bibliographical references and indexes.
Keywords: Poetry -- Collections